REPRESENTATION OF PERSONS WITH DISABILITIES IN THE SERBIAN PRESS: ANALYSIS OF DAILY NEWSPAPERS BLIC AND DANAS - Trajković, Jovana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
Low social awareness of disability issues maintains discriminatory attitudes in society and does not contribute to improving the position of persons with disabilities. The media play a significant role in this because they produce new or reproduce existing meanings through representation. The media represent different identities and act as a forum for the social construction of reality, they construct and reproduce the social definition of disability. А highly discriminatory society is the main reason for the difficult life of people with disabilities, but objective media coverage of the topic of disability and persons with disabilities can improve this situation. Such reporting would contribute to changing the stereotypical attitudes towards which a person with a disability is viewed as one who needs help and pity, without considering physical and cultural barriers created in society. If living conditions were adapted to people with disabilities to the extent that they were adapted to all other persons, the quality of life of persons with disabilities would be significantly improved. In the research conducted for the purposes of this paper, we came to the conclusion that print media in Serbia do not devote sufficient space to the topic of disability, and generally report stereotypically.
Keywords: disability, people with disabilities, media, representation